2002
DOI: 10.1002/jsfa.1108
|View full text |Cite
|
Sign up to set email alerts
|

Shelf‐life extension of refrigerated seabass slices under modified atmosphere packaging

Abstract: The effect of CO 2 -enriched atmosphere in combination with either oxygen or nitrogen on the keeping quality of seabass slices stored at 4°C was investigated. The inhibitory effect on bacterial growth increased proportionally to the CO 2 concentration in the packaging, maximum inhibition being achieved with 100% CO 2 (P < 0.05). Seabass slices stored in CO 2 -enriched atmosphere had lower total volatile base, trimethylamine, ammonia and formaldehyde contents than those stored in air (P < 0.05). However, increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
158
2
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(203 citation statements)
references
References 31 publications
38
158
2
5
Order By: Relevance
“…To our knowledge there is almost no available report on sensory evaluation of B. areolata, so we decided to compare our results with other mollusc. Our results are comparable to Gokoglu (2002) on fresh mussels (Mytilus galloprovincialis) stored at 4°C, which is acceptable up to 4 days, while air packed green mussels (Perna viridis) on polystyrene trays at 4°C were (Masniyom et al, 2011). Cao et al (2009) however reported a higher shelf-life of 10-11 days for Pacific oysters (Crassostrea gigas) stored at 5°C.…”
Section: Sensory Changes Of Babylonia Areolata During Refrigerated Stsupporting
confidence: 84%
“…To our knowledge there is almost no available report on sensory evaluation of B. areolata, so we decided to compare our results with other mollusc. Our results are comparable to Gokoglu (2002) on fresh mussels (Mytilus galloprovincialis) stored at 4°C, which is acceptable up to 4 days, while air packed green mussels (Perna viridis) on polystyrene trays at 4°C were (Masniyom et al, 2011). Cao et al (2009) however reported a higher shelf-life of 10-11 days for Pacific oysters (Crassostrea gigas) stored at 5°C.…”
Section: Sensory Changes Of Babylonia Areolata During Refrigerated Stsupporting
confidence: 84%
“…These results indicate that MDA production depends not only on the amount of oxygen in the package but also on other factors, i.e. the type of microbial flora present (Ruiz-Capillas & Moral 2001), probable inactivation of antioxidative enzymes as a result of carbonic acid production in fish muscle packaged in high CO 2 concentration (Masniyom et al 2002), and CO 2 dissolution in the tissue, which intensify the autoxidation of polyunsaturated fatty acids (Ruiz-Capillas & Moral 2001). According to Auburg (1993), TBA values may not reveal the actual degree of lipid oxidation since MDA can interact with other components of the fish body.…”
Section: Resultsmentioning
confidence: 85%
“…It has been confirmed that fish packaging in modified atmosphere significantly extends the shelf life of the product (Masniyom et al 2002;Stamatis & Arkoudelos 2007;Provincial et al 2010). The most common freshwater fish retailed in the Serbia are carp.…”
mentioning
confidence: 88%
“…Pseudomonas and Shewanella spp), the main spoilage microflora of proteinaceous raw food such as fish when preserved under refrigeration (Gimenez et al 2002). Masniyom et al (2002) reported that CO 2 enters into mass action equilibrium for enzymatic decarboxylation, leading to inhibition of the metabolic activity of the bacterial flora. Beside of inhibitory effect of carbon dioxide on bacterial growth, antibacterial activity of the nisin in the treated rainbow trout could describe lower PVC values in this group compare to the control.…”
Section: Assessment Of Bacteriological Spoilagementioning
confidence: 99%